A taxonomic study on Hypogastrura Bourlet, 1839 (Collembola, Hypogastruridae) from China - Jia, Junli; Skarżyński, Dariusz; Konikiewicz, Marta (Zootaxa, 2011)
A new species of the Hypogastrura trybomi group is described from Shanxi province, China. Because of the presence of prolonged maxillary lamellae and 6 setae on the dens, H. manghe sp. nov. resembles H. hexasetata Jiang & Yin, 2010. H. yosii Stach, 1964, equal to H. sheyangensis Jiang, Tang & Chen, 2010, is redescribed based on syntypes. The latter species was recognized as a junior synonym of the former. A key to the Chinese Hypogastrura Bourlet, 1839 species is also given.